2008
DOI: 10.1186/1471-2105-9-428
|View full text |Cite
|
Sign up to set email alerts
|

SPSmart: adapting population based SNP genotype databases for fast and comprehensive web access

Abstract: Background: In the last five years large online resources of human variability have appeared, notably HapMap, Perlegen and the CEPH foundation. These databases of genotypes with population information act as catalogues of human diversity, and are widely used as reference sources for population genetics studies. Although many useful conclusions may be extracted by querying databases individually, the lack of flexibility for combining data from within and between each database does not allow the calculation of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 9 publications
8
102
4
1
Order By: Relevance
“…Genotype data from West Africans, European Spaniards, Mesoamerican Amerindians, and Han Chinese from Beijing were used as parental populations. These parental allele frequencies were obtained from three sources: reference publications (Martinez-Marignac et al 2007;Tian et al 2007), Hapmap data extracted from the dbSNP at the NCBI webpage, and the 1000 Genomes project downloaded from SPSmart (Amigo et al 2009;Amigo et al 2008). The triangular plots were generated with the package klaR (Weihs et al 2005) on R (Team 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genotype data from West Africans, European Spaniards, Mesoamerican Amerindians, and Han Chinese from Beijing were used as parental populations. These parental allele frequencies were obtained from three sources: reference publications (Martinez-Marignac et al 2007;Tian et al 2007), Hapmap data extracted from the dbSNP at the NCBI webpage, and the 1000 Genomes project downloaded from SPSmart (Amigo et al 2009;Amigo et al 2008). The triangular plots were generated with the package klaR (Weihs et al 2005) on R (Team 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(Sánchez et al 2006;Phillips et al 2007), all genotyped for a panel of 34 AIMs. The genotyping data were compiled using SPSmart (Amigo et al 2008). (B) Structure bar plot indicating ancestral components of L-European mtDNA carriers based on profiles derived from a set of 34 AIMs.…”
Section: Discussionmentioning
confidence: 99%
“…Further examination of the extended haplotype blocks in ASN showed that rs2291725 is highly linked with another 43 SNPs Genotypes were analyzed as described using the SPSmart v3 and Haplotter (Voight et al 2006;Amigo et al 2008). The average frequency of two alleles-derived allele GIP 103C and ancestral chimpanzee allele GIP…”
Section: Variants At the Gip Locus Were Partially Selected In Eurasiamentioning
confidence: 99%